Value Proposition Design for Custom Clothing Startup Using Design Thinking Approach - Astri Ghina; Nurul Afifah (Jurnal Manajemen Indonesia, 2021)
There are thousands of digital-based startups in Indonesia but only few have a sustainable business development. One of the reasons is the products created by startups are not in accordance with market needs. Fashion is one of the startups that has the potential to develop in the digital age, because it is one of the second largest subsectors that contribute to the Indonesian economy. In the field of fashion, especially in customized clothing, the main obstacle experienced by business participants is low competitiveness against those who owns a branded business. This is indicated by dissatisfaction with the quality of the service, which resulted in unfaithful users. This research aims to explore the interaction between custom clothing businesses and their users so that the concerns coming from both parties can be used as the basis for creating digital-based solutions. This research focused in exploring the interaction between tailors and sewing service users using a design thinking approach. Qualitative method is used in this research and information is gathered using survey strategy. Data collection is conducted by in-depth interviews with tailors and sewing service users. Observation is also used to understand the tailor’s daily activities. The result shows that there is concern between tailors and their users. Proposed idea as a digital-based solution is project management with transparent sewing service process that can be seen by sewing service users. This research is limited to the stage of formulating digital feature ideas which can be used as the basis for designing rapid prototypes. Validation of the prototype can be conducted in the next study.